Augmented reality in art education: A narrative synthesis - Yahaya, Sumiyah; Zalay @ Zali, Abdul Aziz (Journal of Islamic, Social, Economics and Development, 2026)
This narrative review examines the integration of augmented reality (AR) in art education, with particular emphasis on pedagogical practices, student-centred learning approaches, and creative applications. By synthesising recent scholarly literature from 2013 to 2025, the review highlights how AR provides interactive, immersive, and multisensory experiences that enhance student engagement, motivation, and conceptual understanding. Thematic analysis identified three primary dimensions of AR implementation: teacher training, learning methods, and applications. Teacher preparedness emerged as a critical factor, with effective integration requiring both technical proficiency and pedagogical competence. Student-centred learning approaches supported by AR facilitate experiential learning, collaborative activities, and creative exploration, enabling learners to visualise abstract concepts, develop spatial reasoning, and build creative confidence. AR applications in art education range from foundational visual literacy in primary and secondary education to advanced creative skill development in higher education, including digital sketching, 3D modelling, virtual exhibitions, and interactive storytelling. Despite its promise, challenges persist, including limited professional development opportunities, insufficient curriculum integration, and the absence of standardised assessment frameworks, which constrain the sustainable adoption of AR in educational settings. The review underscores the need for theoretically grounded, longitudinal, and interdisciplinary research to evaluate long-term learning outcomes, support holistic skill development, and inform scalable AR interventions. By providing a comprehensive synthesis of current trends, challenges, and future directions, this study offers valuable insights for educators, researchers, and policymakers seeking to enhance the quality, relevance, and inclusivity of art education within digitally enriched learning environments.